2006
DOI: 10.7863/jum.2006.25.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm Ultrasonography as an Alternative to Whole-Body Plethysmography in Pulmonary Function Testing

Abstract: These data suggest that dynamic measurements using diaphragm ultrasonography provide a relatively poor measure of pulmonary function in relation to whole-body plethysmography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 15 publications
(26 reference statements)
1
55
0
Order By: Relevance
“…According to some of the authors [18,36] of studies on healthy subjects, no significant relationships were found between the right hemidiaphragmatic excursion and the respiratory function parameters. Others found significant correlations with the degree of air trapping, TLC and FEV 1 /FVC ratio [37], although a different technique was used to establish the excursion.…”
Section: Discussionmentioning
confidence: 99%
“…According to some of the authors [18,36] of studies on healthy subjects, no significant relationships were found between the right hemidiaphragmatic excursion and the respiratory function parameters. Others found significant correlations with the degree of air trapping, TLC and FEV 1 /FVC ratio [37], although a different technique was used to establish the excursion.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in diaphragm mobility has been identified in patients with COPD and has been associated with a decline in pulmonary function parameters. (21) In a previous study, we demonstrated a relationship between diaphragmatic dysfunction and air trapping.…”
Section: Discussionmentioning
confidence: 77%
“…Nevertheless, it was still visible in 72% of patients. Regardless of the approach, the left hemidiaphragm assessment may be more challenging because of gas interference from the stomach and the bowel, which makes it more difficult to visualize [22]. Assessment of the right hemidiaphragm is more feasible because of the diaphragm close contact with the liver surface.…”
Section: Discussionmentioning
confidence: 97%
“…Ultrasound of the diaphragm using B-mode alone [8,11,[13][14][15][16][17][18][19] or combined with M-mode has been described in literature [4,9,[20][21][22]. B-mode is a 2-dimensional imaging, which is used to identify the diaphragm at the interface between the lung and the subphrenic solid organ.…”
Section: Introductionmentioning
confidence: 99%